Freeze-drying platforms design for batch fabrication of Haversian system mimicking scaffolds with enhanced osteogenesis - Lin, Licheng; Huang, Xiuhong; Li, Zhentao; Zhang, Guiyin; Yu, Hongbo; Wan, Yi; Zhou, Changren; Zhou, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Haversian system is one of the most important pathway to repair bone defects，and it is the basic guarantee for the repair of bone defects, which means that the formation of Haversian system indicates the repairing of the defects. The integration of structure and function for tissue engineering scaffolds is of great importance in mimicking native bone tissue. However, in confront to the increasing demands, how to rapidly prepare various sizes of such Haversian system mimicking scaffolds in batch becomes a major challenge. In this study, we designed the three types of platforms with different sizes in combination with freeze-drying approach. Chitosan/type I collagen composite materials were used to study the structure, morphology and performance of the production, and the effects of the controlled architecture on osteogenesis. Results showed that the phys-icochemical effects of the mass fabricated scaffolds of various sizes met the require-ments of bone repair materials. In addition, the scaffolds had good cytocompatibility and excellent in vivo bone repair performance, which have potential clinical applica-tions.